Optical impedance matching with scanning near-field optical microscopy - SHVETS, IGOR (My University, 2003)
We present an experimental study of the coupling of energy from a waveguide into a submicron size optical transmission line (gold on silicon). We demonstrate that the coupling efficiency depends upon the polarization direction. On the condition when a TEM mode is launched in the transmission line we observe a substantial enhancement of the coupling efficiency. The coupling efficiency also depends on the impedance of the transmission line that is in turn determined by its geometry. We have made a prediction of the condition of the maximum coupling efficiency through the approach of impedance matching. We believe these results can be of importance in the development of new concepts for high resolution optical imaging by means of scanning near-field optical microscopy.
PUBLISHED
Keywords: shear-force; polarisation; resolution; light